2008
DOI: 10.1007/s10508-007-9287-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Female Sexual Function Index in a Population Based Sample from Finland

Abstract: The factor structure and reliability of the Female Sexual Function Index (FSFI) was evaluated in a Finnish population based sample of 2,081 women, age 33-43 years. In addition, associations between female sexual function and age, psychological distress, alcohol use, hormone based contraceptives, child sexual abuse (CSA), and adult sexual abuse were examined. The results supported a six factor solution for the FSFI with high internal consistencies, in line with earlier research in clinical populations. Psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 52 publications
11
88
4
2
Order By: Relevance
“…Female sexual function was assessed using the Female Sexual Function Index (FSFI; Rosen et al, 2000), applying a six-factor structure shown to be valid for the current sample by Witting et al (2008). The six factors assessed desire, arousal, lubrication, orgasm, satisfaction, and pain.…”
Section: Instrumentsmentioning
confidence: 99%
“…Female sexual function was assessed using the Female Sexual Function Index (FSFI; Rosen et al, 2000), applying a six-factor structure shown to be valid for the current sample by Witting et al (2008). The six factors assessed desire, arousal, lubrication, orgasm, satisfaction, and pain.…”
Section: Instrumentsmentioning
confidence: 99%
“…Women with CS had significantly lower FSFI scores, while the median of total FSFI scores for patients with CS and the control group were 16.6 [IQR: [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and 26.8 [IQR: 25.5-30.4], respectively (p<0.001). The arousal, lubrication, the ability to achieve orgasm, pain and satisfaction subdomains of FSFI were significantly lower in patients with CS (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The total score ranged between 2-36 points, and a total score of <26.55 indicated sexual dysfunction as described by Wiegel et al and in various studies. [11,13,14] The questionnaire survey was conducted during the early follicular (days 2-5) phase of the participants' menstrual cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Sexual function Cross-sectional analysis of LNG-IUS and copper IUD users using FSFI Prevalence of female sexual dysfunction was lower among LNG-IUS vs copper IUD users [66] Witting et al (2008) Epidemiological study of FSFI in a population sample LNG-IUS was associated with less pain, more desire, arousal, satisfaction, compared with other contraceptive methods [67] Halmesmäki et al…”
Section: Merki-feld Et Al (2008) Expulsion Retrospective Analysis Ofmentioning
confidence: 99%